Anatomical Study of the Grasscutter’s Aorta (Thryonomys swinderianus, Temminck 1827) - Ananivi Sogan; Maman You Esperance Broalet; Mawunyo Afanvi Hounake; Yaovi Edem James; Amegnona Agbonon; Martial Gervais Hounnou (European Scientific Journal, ESJ, 2026)
Rationale and objective: The grasscutter’s aorta, the largest artery in the body from which most other arteries originate, is an important anatomical model. The objective of the study is to describe the grasscutter’s aorta and identify its main branches.Materials and methods: This was a morphological, cross-sectional, descriptive study of the aortas of five adult grasscutters. Euthanasia was performed under general anesthesia by exsanguination via the left ventricle following a thoraco-abdominal incision. Aortic dissections were carried out on fresh specimens after vascular injection of colored latex. The parameters analyzed included the origin, course, termination, dimensions, and major branches.Results: The aorta originates at the base of the left ventricle and terminates at the entrance to the pelvic cavity, following an initial arch before continuing as a nearly midline thoracic and abdominal segment in a cranio-caudal direction. The main branches included two coronary arteries, two supra-aortic trunks, a constant celiac trunk, and either one or two mesenteric arteries. The average length of the aorta was 132.48 mm, with mean diameters of 1.61 mm, 1.46 mm, and 1.04 mm at the ascending aorta, the descending thoracic aorta, and the abdominal aorta, respectively.Conclusion: The grasscutter’s aorta qualitatively presents almost the same main branches as that of humans. Quantitatively, however, certain differences have been identified. Further studies with larger sample sizes are necessary to confirm these initial observations.